2008
DOI: 10.1088/0004-6256/136/1/259
|View full text |Cite
|
Sign up to set email alerts
|

THE SECONDGALEXULTRAVIOLET VARIABILITY (GUVV-2) CATALOG

Abstract: We present the second Galaxy Evolution Explorer (GALEX ) Ultraviolet Variability (GUVV-2) Catalog that contains information on 410 newly discovered time-variable sources gained through simultaneous near (NUV 1750 -2750Å) and far (FUV 1350 -1750Å) ultraviolet photometric observations. Source variability was determined by comparing the NUV and/or FUV fluxes derived from orbital exposures recorded during a series of multiple observational visits to 169 GALEX fields on the sky. These sources, which were contained … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…The largest group of known variable sources listed in the GALEX UV Variability-2 catalog are active galaxies (Wheatley et al 2008). This sample of sources was derived solely through selection due to their observed UV variability, without prior knowledge that such sources were in fact AGN.…”
Section: Introductionmentioning
confidence: 99%
“…The largest group of known variable sources listed in the GALEX UV Variability-2 catalog are active galaxies (Wheatley et al 2008). This sample of sources was derived solely through selection due to their observed UV variability, without prior knowledge that such sources were in fact AGN.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the feasibility of using NUTS for temporal variability studies, we also looked at previous observations of transient events in archival data, particularly from the GALEX mission. We made use of the observations from the variability catalogs (Welsh et al, 2005;Wheatley et al, 2008) and time domain survey (Gezari et al, 2013), as well as additional catalogs of novae outbursts (Wils et al, 2010) and M dwarf flares (Welsh et al, 2007). In addition, there have been new archival studies of short timescale UV variability (de la Vega & Bianchi, 2018;Brasseur et al, 2019) using the gPhoton package (Million et al, 2016).…”
Section: Performance Estimatesmentioning
confidence: 99%
“…The system was categorized as a high-amplitude variable in the second version of the GALEX Ultraviolet Variability (GUVV-2) Catalog (Wheatley et al 2008), where a maximum NUV flux difference of two magnitudes was identified within the available visits at that time. Welsh et al (2006) studied one of CR Draconis' flare events with high temporal sampling by extracting light curves from sky-projected, "extended" (-x) photon list files, produced as non-standard products of the GALEX mission pipeline.…”
Section: Example Science Application -Stellar Flares From Cr Draconismentioning
confidence: 99%